Pagamea spruceana (Rubiaceae, Gaertnereae), a new species from flooded white-sand forests in the upper Rio Negro region, Brazil - Prata, Eduardo Magalhães Borges; Carvalho, Rangel Batista de; Vicentini, Alberto (Phytotaxa, 2016)
Pagamea spruceana, a new species from Northwestern Amazon, Brazil, is endemic to the Upper Rio Negro region, in the Içana and Uaupés River Basins, and differs from other functionally dioecious species of Pagamea by its capitate and puberulous inflorescences and narrowly elliptic leaf blades with revolute and puberulous margins. Pagamea spruceana is the only species in the genus known from long-term inundated habitats (igapós) in the Amazon. The new species is here described and the affinities with morphologically similar and closely related species are discussed. © 2016 Magnolia Press.